The Palatability of Lopinavir and Ritonavir Delivered by an Innovative Freeze-Dried Fast-Dissolving Tablet Formulation - David W. Pittman; Alexandra M. Brantly; Alexandra L. Drobonick; Hannah T. King; Daniel C. Mesta; Caroline G. Richards; Manjari Lal; Manshun Lai (AIDS Research and Treatment)
Negative hedonic sensory qualities of HIV antiretroviral drugs often reduce patient adherence particularly in pediatric populations requiring oral consumption. This study examines the palatability of an innovative delivery mechanism utilizing a freeze-drying-in-blister approach to create fast-dissolving tablets (FDTs) containing a fixed-dose combination of lopinavir and ritonavir (LPV/r). Consumption patterns of solutions during brief-access and long-term testing and baby foodstuff consumption were analyzed to evaluate the orosensory detection and avoidance of placebo FDTs containing no LPV/r (FDT−) and FDTs containing LPV/r (FDT+). Rats showed no change in consumption patterns for the placebo FDT− compared with control solutions. Rats can detect but do not avoid FDT+ at body-weight-adjusted dosages in both brief-access (30-s) and long-term (23 h) consumption tests. There is an aversive response to concentrated doses of FDT+ during brief-access tests that cannot be masked by 25% sucrose. However, the strongest FDT+ concentration was not rejected when mixed with 50 g of applesauce, banana sauce, or rice cereal baby foodstuffs. The averseness of the FDT+ was associated with the presence of LPV/r and not the FDT− formulation itself. The novel FDT formulation appears to be a palatable delivery mechanism for oral antiretroviral pharmaceuticals especially when mixed with baby foodstuffs.